The effect of voiding position on uroﬂowmetry ﬁndings of patientswith Benign Prostatic Obstruction(BPO) in urology clinic HTAA - Redzuan, Muhd Zaki Azre; Kamarulzaman, Mohd Nazli; Ghazali, Hamid (John Wiley & Sons, 2016)
Introduction: Changes in voiding positionmay have signi ﬁcant impact on micturitiondue to factors such as changes in pressureof abdominal muscles and viscera, andrelaxation of pelvic ﬂoor muscles in differ-ent voiding positions. Few studies in the lit-erature have addressed the impact ofvoiding position on uroﬂowmetric results,however, the results were inconclusive.Objectives: To investigate the uroﬂowme-try ﬁndings of three different voiding posi-tions in BPO patients attending theUrology Clinic, HTAA.Materials and Methods: Cross-sectionalobservational study of BPO patientsattending the Urology Clinic HTAA fromMarch 2015 to December 2015.Uroﬂowmetry in standing, sitting andsquatting positions were done in those ful-ﬁlling the study criteria. The maximumﬂow rate, average ﬂow rate, voiding vol-ume, total voiding time and post-voidingresidual volume were measured andrecorded. The results were then comparedand analysed. Other factors such as nor-mal voiding habit, number of medication,size of prostate, severity of BPO andintravesical prostatic protrusion (IPP) werealso studied for any signiﬁcance.Results: A total of 123 patients were stud-ied. Majority of patients were more than60 years old (87%) and more than halfwere Chinese (58.5%) followed by Malays(35%) and Indians (5.7%). The commonestvoiding positions among these patientswere standing (78%), sitting, 15 patients(12.2%) and squatting, 12 patients (9.8%).Average IPSS was 12 and majority of themwere in the moderate group (63.4%). Themean size of prostate in this study was42.95 grams. 33 patients had IPP (27.27%)while the rest (72.72%) did not have IPP